Re-evaluation of the conodont Iapetognathus and implications for the base of the Ordovician System GSSP - Terfelt, Fredrik; Bagnoli, Gabriella; Stouge, Svend (Lethaia, 2011)
In 2000, the International Union of Geological Sciences (IUGS) ratified the decision from the International Working Group on the Cambrian–Ordovician Boundary (COBWG) to place the Global boundary Stratotype Section and Point (GSSP) for the base of the Ordovician System in the Green Point section, Newfoundland, Canada, at a point coinciding with the first appearance of the conodont Iapetognathus fluctivagus. However, a restudy of the conodont successions from Green Point shows that this species is not present at the boundary interval, and as a consequence the section does not fulfil the biostratigraphical requirements of a GSSP. The GSSP horizon as now defined is based on a level part-way through the range of I. preaengensis – a species with lower first appearance datum (FAD). The true FAD of I. fluctivagus is above the FAD of planktonic graptolites and well above the FAD of I. preaengensis. As a consequence of these problems, a restudy of the GSSP section and the other sections in the Cow Head Group is necessary. A redefinition of the GSSP horizon is suggested. The following four alternative horizons have potential as new horizons for the GSSP level: the FAD of Cordylodus intermedius; the FAD of Cordylodus andresi; the FAD of Eoconodontus notchpeakensis; and the FAD of the agnostoid Lotagnostus americanus.